PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DISKUSI DAN PERCAYA DIRI SISWA SMP - Wikanengsih; Ruhiman; Rostikawati, Yeni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to determine: 1) the effectiveness of the application of the problem-based learning (PBL) model assisted by visual media in improving the ability (writing) of discussion texts and students' self-confidence; 2) correlation between self-confidence and ability to write discussion text; 3) describe student performance during learning to write discussion texts using problem-based learning methods assisted by visual media. The type of research is quasi-experimental with the student population of MTsN 2 West Bandung; 4) students' difficulties in writing exposition texts. The research sample was class IX E as the control class, and class IX F as the experimental class. There are 30 students in each class. The results showed: 1) the ability to write discussion texts and the confidence of MTs students who studied using the PBL model with the aid of visual media were better than students who learned using conventional methods; 2) there is a correlation between self-confidence and the ability to write discussion texts; 3) During the implementation of this PBL model, the activities of teachers and students were categorized as very good. The results of the final knowledge test show that the average acquisition of the experimental class is in the medium category, while the control class shows the poor category. The average final skill score shows that the experimental class gets a better score than the control class. The difficulties experienced by the two classes during the practice of writing discussion texts generally lie in the activity of assembling sentences into a complete text according to the structure and rules and concluding controversial arguments.